Penggunaan Media Visual Terhadap Hasil Belajar Fiqh di SMP Babus Salam Kota Tangerang - basyit, abdul; Sihabudin, Ahmad; Heri, Totong; Gumelar, R Tommy; Zulaikha, Lulu Nur (Universitas Muhammadiyah Prof Dr Hamka, 2025)
This study aims to determine the effectiveness of the use of visual media on student learning outcomes in fiqh subjects in class VIII of SMP Babus Salam Karawaci, Tangerang City. The background of this research is the low interest and learning outcomes of students due to the use of monotonous learning methods. The research method used is quantitative with a quasi-experimental approach using pretest-posttest control group design. The research sample amounted to 62 students which were divided into two groups, namely the experimental class and the control class. Data collection instruments in the form of objective tests and Likert scale questionnaires. The results of the study show a sig value of 0.000 <0.05 so there is a significant difference between the learning outcomes of the experimental class and the control class. So it can be concluded that the use of visual media has an effective effect on learning outcomes in fiqh subjects.